Parametric analysis of straw wad destroyer - Yury Ivanovich Yermolyev; Artem Alexandrovich Doroshenko; Igor Аlexandrovich Ivashchenko; Roman Evgenyevich Fomenko (Advanced Engineering Research, 2015)
The research subject is an analytical modeling and multivariate analysis of the straw wad destruction by the cutting cylinder with radial fingers and a horizontal axis of rotation. The work objective is the detection of regularities for straw wad destruction under the geometric and kinematic parameter variation of the gear for wad breaking. The research objective is the impact assessment of the geometric parameters, composition and kinematics of the straw wad destroyer on its performance indices. The investigative technique is an analytical modeling. The effect of the fingers length, their number, cylinder chopper rotation velocity, its arrangement in respect to the straw wad, straw wad conveyorized infeed on the straw wad destruction process is estimated. It is found how the factors considered and their parameters affect the direction and range of the culm ejection from the drum destroyer fingers taking into account how the flying straws hit the next element of the operative parts system. The spatial arrangement rationality of the drum destroyer, its geometric and kinematic parameters for the processing properties of straw bales, and the specified variability interval of the performance values of the technological device is preevaluated. It is established that the process of bale destruction, the movement of straws on the fingers, and the trajectory of their movement in the air, depends significantly on the operating width of the finger gripping the straw wad.